2021
DOI: 10.1016/j.omtn.2021.10.020
|View full text |Cite
|
Sign up to set email alerts
|

11C-radiolabeled aptamer for imaging of tumors and metastases using positron emission tomography- computed tomography

Abstract: Identification of primary tumors and metastasis sites is an essential step in cancer diagnostics and the following treatment. Positron emission tomography-computed tomography (PET/CT) is one of the most reliable methods for scanning the whole organism for malignancies. In this work, we synthesized an 11 C-labeled oligonucleotide primer and hybridized it to an anti-cancer DNA aptamer. The 11 C-aptamer was applied for in vivo imaging of Ehrlich ascites carcinoma and its metastases in mice using PET/CT. The imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In a simplified case of MNP binding to a membrane in its specific area, limited by the size of the aptamer (within 10 nm [117]), as well as a fragment of fibronectin fiber and integrin, the character of particle motion is an arc, the length of which is limited by the contact condition membrane particle on the left and right, as shown in figure 1. It is also important to note that MNP deforms the membrane at the site of contact with it and, during rotation, creates a moment of force that has a vertical projection, which is applied to the transmembrane protein integrin (or to another membrane element with which a connection can selectively occur)…”
Section: Model Of Mechanical Interaction Of Mnps With a Cell Membranementioning
confidence: 99%
“…In a simplified case of MNP binding to a membrane in its specific area, limited by the size of the aptamer (within 10 nm [117]), as well as a fragment of fibronectin fiber and integrin, the character of particle motion is an arc, the length of which is limited by the contact condition membrane particle on the left and right, as shown in figure 1. It is also important to note that MNP deforms the membrane at the site of contact with it and, during rotation, creates a moment of force that has a vertical projection, which is applied to the transmembrane protein integrin (or to another membrane element with which a connection can selectively occur)…”
Section: Model Of Mechanical Interaction Of Mnps With a Cell Membranementioning
confidence: 99%
“…206 Since then, various radiolabeling strategies for SPECT or PET have been developed, including the use of isotopes, such as 99m Tc, 111 In, and 123 I for SPECT, and 11 C, 18 F, 68 Ga, and 64 Cu for PET. [207][208][209][210][211] Bohrmann et al developed an aptamer-targeted nanoplatform based on hyperbranched polyglycerol (HPG) to improve the stability and applicability of aptamer. 210 Their study demonstrated that the Sgc8 aptamer exhibited highly specic binding to various cancer cells and displayed good binding characteristics and biocompatibility in vitro, with an extended half-life.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…Ozerskaya et al . took an interesting approach for 11 C labeling of AS-14 aptamer for PET imaging of Ehrlich ascites carcinoma 93 . Instead of directly labeling the aptamer, a 11 C-labeled complementary primer was hybridized to AS-14.…”
Section: Modalities For Aptamer Imagingmentioning
confidence: 99%